Sporting spirit - The Star, (2011)
TEAM Vatica FC of Universiti Putra Malaysia emerged champion of the inter-varsity Datuk Haji Suhaimy Futsal Tournament recently when it beat Universiti Pendidikan Sultan Idris (UPSI)'s team Unimax FC 2-0 in the final match of the higher learning institutions (IPTA/IPTS) category.